Energy evaluation of algal cell disruption by high pressure homogenisation. (May 2015) - Yap, Benjamin H.J.; Dumsday, Geoff J.; Scales, Peter J.; Martin, Gregory J.O.
Highlights: Energy required for high pressure homogenisation of microalgae was analysed. Solids content, TAG content, and homogenisation pressure were considered. Processing of concentrated microalgal paste is not only possible but also required. Between 6% and 110-times of the energy density of the biodiesel was required. HPH is feasible for concentrated pastes of relatively weak microalgae. Abstract: The energy consumption of high pressure homogenisation (HPH) was analysed to determine the feasibility of rupturing algal cells for biodiesel production. Experimentally, the processing capacity (i.e. flow rate), power draw and cell disruption efficiency of HPH were independent of feed concentration (for Nannochloropsis sp. up to 25% w/w solids). Depending on the homogenisation pressure (60–150 MPa), the solids concentration (0.25–25% w/w), and triacylglyceride (TAG) content of the harvested algal biomass (10–30%), the energy consumed by HPH represented between 6% and 110-times the energy density of the resulting biodiesel. Provided the right species (weak cell wall and high TAG content) is selected and the biomass is processed at a sufficiently high solids concentration, HPH can consume a small fraction of the energy content of the biodiesel produced. This study demonstrates the feasibility of process-scale algal cell disruption by HPH based on its energy requirement.